Wet and dry faults at thrust fronts as indicators of paleofluid flow in the carbonates of the Geneva Basin (Switzerland, France) - G.L. Cardello; M. Lupi; E. Carminati; C. Doglioni; M. Sartori; E. Samankassou; M. Meyer (Geothermics, 2026)

Chemostratigraphy and 40Ar/39Ar geochronology of Ventotene volcano (Pontian Islands, Tyrrhenian Sea): The missing link in the Quaternary potassic magmatism of central Italy - G.L. Cardello; A.M. Conte; M. Gaeta; B. Jicha; F. Lombardi; L. Monaco; S. Nomade; C. Perinelli; M. Petrelli; G. Sottili; D.M. Palladino (Quaternary Science Reviews, 2026)

Subsurface characterization of crystalline rocks at the Einstein Telescope candidate site (Italy): Insights from seismic tomography, geoelectrical and morphostructural analyses - F. Villani; S. Maraio; L. Improta; P.M. De Martini; D. Cavallaro; M. Firetto Carlino; C.A. Brunori; V. Longo; L. Casini; M.C. Caradonna; C. Zei; S. Rapisarda; et al. (Tectonophysics, 2025)

Consumer evaluations of commercially available plant-based cheddar cheese alternatives reveal inferior taste, nutrition and emotional appeal - Sara R. Jaeger; David Jin; Christina M. Roigard; Armand V. Cardello (Food Research International, 2025)

Carbonate deformation through the brittle-ductile transition: The case of the SW Helvetic nappes, Switzerland - Giovanni Luca Cardello; Stefano M. Bernasconi; Maria Giuditta Fellin; Meinert Rahn; Ricarda Rosskopf; Colin Maden; Neil S. Mancktelow (Journal of Structural Geology, 2024)

Causes of mortality in wild European hedgehog (Erinaceus europaeus) populations in Italy and Switzerland - I. Prandi; E. Dervas; E. Colombino; L. Bertolotti; M. Cardello; D. Ippolito; M. Perotti; M. Vacchetta; S. Zanet; M. Mauthe Von Degerfeld; G. Quaranta; U. Hetzel; et al. (Journal of Comparative Pathology, 2024)

The Volsci Volcanic Field (central Italy): eruptive history, magma system and implications on continental subduction processes - F. Marra; G. L. Cardello; M. Gaeta; B. R. Jicha; P. Montone; E. M. Niespolo; S. Nomade; D. M. Palladino; A. Pereira; G. De Luca; F. Florindo; A. Frepoli; et al. (International Journal of Earth Sciences, 2021)
Here, we report on the Quaternary Volsci Volcanic Field (VVF, central Italy). In light of new 40 Ar/ 39 Ar geochronological data and compositional characterization of juvenile eruptive products, we refine the history of VVF activity, and outline the implications on the pre-eruptive magma system and the continental subduction processes involved. Different from the nearby volcanic districts of the Roman and Campanian Provinces, the VVF was characterized by small-volume (0.01–0.1 km 3 ) eruptions from a network of monogenetic centers (mostly tuff rings and scoria cones, with subordinate lava occurrences), clustered along high-angle faults of lithospheric depth. Leucite-bearing, high-K (HKS) magmas (for which we report for the first time the phlogopite phenocryst compositions) mostly fed the early phase of activity (∼761–539 ka), then primitive, plagioclase-bearing (KS) magmas appeared during the climactic phase (∼424–349 ka), partially overlapping with HKS ones, and then prevailed during the late phase of activity (∼300–231 ka). The fast ascent of primitive magma batches is typical of a tectonically controlled volcanic field, where the very low magma flux is a passive byproduct of regional tectonic strain. We suggest that the dominant compressive stress field acting at depth was accompanied by an extensional regime in the upper crust, associated with the gravity spreading of the Apennine chain, allowing the fast ascent of magma from the mantle source with limited stationing in shallow reservoirs.